LIQUID BIOFERTILIZER AND COMPOST FROM ORGANIC MARKET WASTE - Sriwuryandari, Lies; Sembiring, Tarzan (LIPI Press, 2010)
Liquid biofertilizer and compost from organic market waste were produce by the addition of some functional microorganisms. Azospirrillium sp., Azotobacter sp., Lactobacillus sp., Pseudomonas sp. and Actinomycetes were inoculated into liquid or solid raw materials. The ripe biofertilizer were characterized and meets the Indonesian National standards for biofertilizer. Actinomycetes contained in the liquid fertilizer about 2.95 x 108 cfu/ml, which is meet the standard (? 104 cfu/ml) and other functional microorganisms namely Lactobacillus sp., Azospirillium sp., Azotobacter sp., Pseudomonas sp. and phosphate diluters were grown enormously with the population of more than 105 cfu/ml respectively. Qualitative test of the fertilizer shown that the fertilizer are effective for the crops such as Long bean (Vigna unguiculata), Cucumber (Cucumis sativus), Leek (Allium ampeloprassum) and others. Production of biofertilizer using organic market waste support the organic farming and the national policy on the fertilizer.